2023
DOI: 10.1001/jamanetworkopen.2022.54221
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Importance of Clonal Hematopoiesis in Metastatic Gastrointestinal Tract Cancers

Abstract: ImportanceClonal hematopoiesis (CH) has been associated with development of atherosclerosis and leukemia and worse survival among patients with cancer; however, the association with cancer therapy efficacy, in particular immune checkpoint blockade (ICB), and toxicity has not yet been established. Given the widespread use of ICB and the critical role hematopoietic stem cell–derived lymphocytes play in mediating antitumor responses, CH may be associated with therapeutic efficacy and hematologic toxicity.Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This study found that CH was associated with reduced overall survival in the esophagogastric cancers and had a null effect in colorectal cancers—although DNMT3A mutation status was not independently evaluated as in the FIRE-3 trial analysis. 62 …”
Section: Current Insights Into Ch and Solid Cancermentioning
confidence: 99%
“…This study found that CH was associated with reduced overall survival in the esophagogastric cancers and had a null effect in colorectal cancers—although DNMT3A mutation status was not independently evaluated as in the FIRE-3 trial analysis. 62 …”
Section: Current Insights Into Ch and Solid Cancermentioning
confidence: 99%
“…Early diagnosis and patient prognosis remain formidable challenges due to the subtle symptoms at onset and during tumor invasion and metastasis [ 5 7 ]. Advances in medical science have led to the widespread use of diagnostic techniques such as endoscopy, tissue biopsy, and imaging technology for the diagnosis and management of gastrointestinal tract cancers [ 8 , 9 ]. These essential tools allow the identification of the precise location and severity of the specific lesions [ 10 – 13 ].…”
Section: Introductionmentioning
confidence: 99%